Precision Teaching and Learning Performance in a Blended Learning Environment - Yin, Bin; Yuan, Chih-Hung (Frontiers in Psychology, 2021)
Blended learning has gained increasing popularity in colleges and universities with mixed results. Precision teaching can effectively promote learning performance. The relation between perceived precision teaching and the learning performance of college students in a blended learning environment is investigated in this paper. In the research survey featuring a structural model, 256 college students who attended blended learning courses featuring precision teaching participated. The model results revealed that perceived precision teaching is directly and positively related to self-efficacy and learning motivation. Self-efficacy and learning motivation are directly and positively related to cognitive, teaching, and social presence. Additionally, cognitive, teaching, and social presence are directly and positively related to learning performance. Therefore, perceived precision teaching is remotely and indirectly related to learning performance. These findings provide a new perspective for the theoretical study on blended learning performance and provide a realistic reference for precision teaching practice in the blended learning environment.